2022
DOI: 10.1021/acs.jpca.1c10657
|View full text |Cite
|
Sign up to set email alerts
|

Excited-State N Atoms Transform Aromatic Hydrocarbons into N-Heterocycles in Low-Temperature Plasmas

Abstract: The direct formation of N-heterocycles from aromatic hydrocarbons has been observed in nitrogen-based lowtemperature plasmas; the mechanism of this unusual nitrogenfixation reaction is the topic of this paper. We used homologous aromatic compounds to study their reaction with reactive nitrogen species (RNS) in a dielectric barrier discharge ionization (DBDI) source. Toluene (C 7 H 8 ) served as a model compound to study the reaction in detail, which leads to the formation of two major products at "high" plasma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…The discovery of new N 2 transitions forbidden by the spin-selection rule and induced by SOC perturbation is an important part of optical nitrogen monitoring at different altitudes. The intensity origin of the known emission bands that are forbidden by the electric dipole selection rules is also an important task of N 2 spectroscopy ( Deslandres, 1902 ; Wilkinson and Mulliken, 1959 ; Brown and Winkle, 1970 ; Lofthus and Krupenie, 1977 ; Werner et al, 1984 ; Partridge et al, 1988 ; Piper, 1993 ; Minaev et al, 1995 ; Lewis et al, 2008 ; Ndome et al, 2008 ; Hochlaf et al, 2010a ; Ni et al, 2017 ; Begley et al, 2022 ). This work presents multi-reference configuration interaction (MRCI) calculations of the highly excited states of the nitrogen molecule and an explanation of the intensity origin of several forbidden optical transitions.…”
Section: Energy Harvesting By Triplet States Of Nitrogenmentioning
confidence: 99%
See 3 more Smart Citations
“…The discovery of new N 2 transitions forbidden by the spin-selection rule and induced by SOC perturbation is an important part of optical nitrogen monitoring at different altitudes. The intensity origin of the known emission bands that are forbidden by the electric dipole selection rules is also an important task of N 2 spectroscopy ( Deslandres, 1902 ; Wilkinson and Mulliken, 1959 ; Brown and Winkle, 1970 ; Lofthus and Krupenie, 1977 ; Werner et al, 1984 ; Partridge et al, 1988 ; Piper, 1993 ; Minaev et al, 1995 ; Lewis et al, 2008 ; Ndome et al, 2008 ; Hochlaf et al, 2010a ; Ni et al, 2017 ; Begley et al, 2022 ). This work presents multi-reference configuration interaction (MRCI) calculations of the highly excited states of the nitrogen molecule and an explanation of the intensity origin of several forbidden optical transitions.…”
Section: Energy Harvesting By Triplet States Of Nitrogenmentioning
confidence: 99%
“…In contrast, the ground state of the nitrogen molecule possesses zero spin and several high-energy triplet excited states with deep potential wells. The lowest of them, , can harvest a stock of 6.22 eV energy, being a strongly metastable triplet state with a relatively long radiative lifetime (τ r ) of 2 s ( Brown and Winkle, 1970 ; Minaev et al, 1995 ; Begley et al, 2022 ). Accounting for the short UV wavelength of the transition, this τ r value is indeed unusually large.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…While these studies focus on generating intact molecular ions, N‐addition product ions [M + N] + of alkylbenzenes have been reported in APCI 24 and for volatile saturated hydrocarbons in electric fields 25 . Previously, we investigated the formation of these products for aromatic hydrocarbons in a DBDI and found that excited state N‐atoms N( 2 P) can react with aromatic hydrocarbon cations [M] •+ in the source to form either N‐addition or ‐replacement products 26 . We hypothesized that the reaction could be used to discriminate alkylbenzene isomers based on steric hindrance of the isomers, without the addition of special reagents.…”
Section: Introductionmentioning
confidence: 99%